Empowerment of TPQ Jungsemi Village Towards the Development of Reading and Writing Al-Qur'an of Jungsemi Village Students - Ahmad Habib Alfan Syihab; Fadli Telu Muski Azami; Lainatul Mudzkiyyah (Universitas Kristen Indonesia Toraja, 2024)
Empowerment of the Jungsemi Village Al-Qur'an Education Park (TPQ) in improving the Al-Qur'an reading and writing skills of students is the focus of this research. This research aims to describe the efforts made by TPQ Jungsemi Village to empower students and their impact on improving students' ability to read and write the Al-Qur'an. The research method used is qualitative with a descriptive approach. The research results show that TPQ Jungsemi Village has carried out various empowerment efforts, such as developing interesting learning methods, using technology, and coaching Koran teachers. These efforts are written in the Al-Qur'an by the students